Plasmonic Terahertz Nonlinearity in Graphene Disks. Issue 2 (18th December 2021) - Han, Jeong Woo; Chin, Matthew L.; Matschy, Sebastian; Poojali, Jayaprakash; Seidl, Angelika; Winnerl, Stephan; Hafez, Hassan A.; Turchinovich, Dmitry; Kumar, Gagan; Myers-Ward, Rachael L.; Dejarld, Matthew T.; Daniels, Kevin M.; et al.
Abstract : The discovery of graphene and its unique optical and electronic properties has triggered intense developments in a vast number of optoelectronic applications, especially in spectral regions that are not easily accessible with conventional semiconductors. Particularly in the THz regime, where the free‐carrier interaction with low‐energetic photons usually dominates, detectors and modulators based on graphene often feature an improved response time. Nevertheless, the light−matter interaction suffers from the small interaction volume. One way to enhance the efficiency of such devices at elevated frequencies is by patterning graphene into plasmonic structures like disks. In addition to the increased linear absorption, the plasmon resonance also creates a strong, surface‐localized field that enhances the nonlinear optical response. While experimental studies so far have focused on hot carrier effects, theoretical studies also suggest an increase in the nonlinearity beyond thermal effects. Herein, polarization‐dependent pump‐probe measurements on graphene disks that disentangle the contributions of thermal and plasmonic nonlinearity are presented. An increase in the pump‐induced transmission is observed when pump and probe radiation are copolarized. To further elucidate the interplay of thermal and plasmonic effects, a model that supports the origin of the polarization‐dependent enhancement of the observed THz nonlinearities is developed. Abstract : Graphene plasmonic elements like disks can strongly enhance the light−matter interaction in the THz regime and thus improve optoelectronic devices. Furthermore, the nonlinear response to an intense THz pulse is increased due to the surface‐localized fields. Polarization‐resolved pump‐probe measurements and simulations reveal the nature of this nonlinear response that is governed by thermal effects and Kerr nonlinearity.